2023
DOI: 10.1177/20406207231170701
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factor IX Fc prophylaxis reduces pain and increases levels of physical activity, with sustained, long-term improvements in patients with hemophilia B: post hoc analysis of phase III trials using patient-reported outcomes

Abstract: Background: Pain is a common symptom of hemophilia that may adversely affect patients’ quality of life (QoL). Previous post hoc analyses of prophylaxis with recombinant factor IX Fc fusion protein (rFIXFc) have been published for adults and adolescents, demonstrating improvements in health-related QoL (HRQoL) when assessed by the haemophilia-specific QoL (HaemAQoL) questionnaire. Objective: To describe in depth the evolution of QoL, pain- and activity-related domains and questions for pediatric, adolescent, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…In that study, significant and sustained improvements were observed in the overall Haem-A-QoL score, as well as the subdomains of ‘ physical health ’, ‘ sports and leisure ’, ‘ treatment ’, and ‘ view of self ’. 29 Similarly, a HRQoL study of patients with hemophilia A treated with turoctocog alfa pegol for 6–27 months reported improvements from baseline in both Haem-A-QoL domains ‘ physical health ’ and ‘ feeling ’, and improvements in the domain of ‘ sport ’ in patients previously treated on-demand. 30 These observations are consistent with documented benefits of extended half-life (EHL) factor treatments, namely higher trough levels for clotting factors in patients, resulting in reduced risk of both clinically evident and subclinical bleeds.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In that study, significant and sustained improvements were observed in the overall Haem-A-QoL score, as well as the subdomains of ‘ physical health ’, ‘ sports and leisure ’, ‘ treatment ’, and ‘ view of self ’. 29 Similarly, a HRQoL study of patients with hemophilia A treated with turoctocog alfa pegol for 6–27 months reported improvements from baseline in both Haem-A-QoL domains ‘ physical health ’ and ‘ feeling ’, and improvements in the domain of ‘ sport ’ in patients previously treated on-demand. 30 These observations are consistent with documented benefits of extended half-life (EHL) factor treatments, namely higher trough levels for clotting factors in patients, resulting in reduced risk of both clinically evident and subclinical bleeds.…”
Section: Discussionmentioning
confidence: 95%
“… 12 , 18 20 The Haem-A-QoL improvements observed reflect those of a study by Astermark et al . 29 into the long-term effects of recombinant factor IX Fc fusion protein in adults and adolescents with hemophilia B. In that study, significant and sustained improvements were observed in the overall Haem-A-QoL score, as well as the subdomains of ‘ physical health ’, ‘ sports and leisure ’, ‘ treatment ’, and ‘ view of self ’.…”
Section: Discussionmentioning
confidence: 97%